Performance of large-diameter studs in thin ultra-high performance concrete slab. (December 2021) - Xu, Qizhi; Lu, Kaiwei; Wang, Jingquan; Yao, Yiming
Abstract: Ultra high-performance concrete (UHPC) is becoming a promising solution in steel–concrete composite bridges to improve the structural performance and durability of bridge decks. In contrast with conventional concrete, the excellent properties of UHPC allow for thinner and lighter designs with more efficient connections. In this study, the feasibility of large-diameter (30 mm) stud connection in thin UHPC slab was investigated to fully utilize the mechanical advantages of UHPC. The proposed composite structures employed large-diameter short stud (aspect ratio of 2.0) and UHPC slab as thin as 75 mm. Push-out tests were performed on 15 specimens with varying stud length, diameter and slab thickness. The use of large-diameter studs significantly increased the shear strength and ensured desirable failure mode of stud fracturing. The reduction of slab thickness from 150 to 75 mm resulted in little change to the shear strength, but splitting cracks appeared on the outer slab surface. Marginal effect on the shear strength was observed for large-diameter studs as the stud aspect ratio decreased from 4 to 2 and the cover thickness was reduced to 15 mm. The test results showed two main failure modes, including stud fracture via local crushing and stud fracture with UHPC pry-out. Finite element model was established to further study the stud-UHPC composite mechanism. These findings demonstrated the suitability of using short large-diameter stud and thin UHPC slab to reduce the self-weight and improve shear performance of composite structures.